Influence of initial chemical composition and characteristics of pulps on the production and properties of lignocellulosic nanofibers - Ehman, Nanci Vanesa (2020)
This work aimed to study the influence of the initial chemical composition (glucans, lignin, xylan, and mannans), intrinsic viscosity, and carboxylate groups of pulps on the production process and final properties of lignocellulosic nanofibers (LCNF). Pulps of pine sawdust, eucalyptus sawdust, and sugarcane bagasse subjected to conventional pulping and highly oxidized processes were the starting materials. The LCNF were obtained by TEMPO mediated oxidation and mechanical fibrillation with a colloidal grinder. The nanofibrillation degree, chemical charge content, rheology, laser profilometry, cristallinity and atomic force microscopy were used to characterize the LCNF. The carboxylate groups, hemicelluloses and lignin of the initial pulps were important factors that affected the production process of LCNF. The results revealed that intrinsic viscosity and carboxylate groups of the initial pulps affected LCNF production process, whereas lignin and hemicelluloses influenced the viscosity of LCNF aqueous suspensions, the roughness of LCNF films, and the carboxylate groups content of LCNF.